THE INFLUENCE OF ECONOMIC LITERACY AND ADVERTISING ON CONSUMPTIVE BEHAVIOR IN STUDENTS OF THE FACULTY OF ECONOMICS, STATE UNIVERSITIES (NON-POLYTECHNIC) THROUGHOUT JABODETABEK CLASS OF 2018: PENGARUH LITERASI EKONOMI DAN TERPAAN IKLAN TERHADAP PERILAKU KONSUMTIF PADA MAHASISWA FAKULTAS EKONOMI PERGURUAN TINGGI NEGERI (NON POLITEKNIK) SELURUH JABODETABEK ANGKATAN 2018 - Kenny Leonaltus; Harya Kuncara Wiralaga; Dicky Iranto (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
The consumptive behavior of students from the economics faculty of state universities (non-polytechnics) throughout Jabodetabek class 2018 is certainly influenced by the internal and external conditions of students. The high and low consumptive behavior of students can be influenced by many factors. This study aims to determine the effect of Economic Literacy and Advertising Exposure on Consumptive Behavior of students from the economics faculty of state universities (non-polytechnics) throughout Jabodetabek class of 2018. This research is associative research. The objects of this research are students of the economics faculty of state universities (non-polytechnics) throughout Jabodetabek class 2018, with an unknown population. The sample of this study amounted to 272 respondents determined by the table formula Isaac and Michael. The analytical method used in this research is multiple regression analysis. The results of this study indicate that, economic literacy and advertising exposure partially affect consumptive behavior. The economic literacy variable has a negative and significant impact on consumptive behavior, while the advertising exposure variable has a positive and significant impact on consumptive behavior